NURSING LEADERSHIP STYLE AND PATIENT SAFETY: A SYSTEMATIC LITERATURE REVIEW - Sendy Ayu Mitra Uktutias; Ferry Efendi (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Background: Goal 3 of the Sustainable Development Goals (SDGs) emphasizes Universal Health Coverage (UHC), which aims to ensure access to affordable, safe, effective, and high-quality health services for all. Patient care is delivered through systematically organized stages of activity through a system designed to prevent and mitigate errors. Leadership commitment to safety is a critical component of this system. Aims: To systematically review and analyze the relationship between nursing leadership styles and patient safety outcomes. Methods: This study employed a Systematic Literature Review (SLR) approach following the Preferred Reporting Items for Systematic Reviewers and Meta-Analysis (PRISMA) stages. The literature search used the online databases Scopus, PubMed, and CINAHL with keywords related to leadership, nursing, and patient safety combined with Boolean operators. This study determined the eligibility criteria using PICOS. After the selection process, 14 articles were determined to be eligible for review. Results: The findings indicate that transformational leadership is the most frequently reported and is consistently associated with patient safety, particularly in terms of safety culture, incident reporting, and reduction of clinical errors. Conclusion: Leadership style plays a strategic role in improving patient safety. Transformational nursing leadership demonstrates consistent on the clinical context. Further research is needed to empirically compare the effectiveness of leadership styles, particularly transformational leadership, in relation to patient safety. Keywords: leadership, nurse, patient safety, quality of health care.